A high capacity tunable retransmission type frequency coded chipless radio frequency identification system. Issue 9 (21st May 2019) - Aslam, Bilal; Azam, Muhammad A.; Amin, Yasar; Loo, Jonathan; Tenhunen, Hannu
Abstract: This article presents a 12‐bit frequency coded chipless RFID system in the frequency range of 3 to 6 GHz. The system consists of a fully printable chipless tag and a pair of high‐gain reader antennas. The tag also incorporates its own antennas to improve the read range. Information is encoded into frequency spectrum using a multi‐resonant circuit. The circuit consists of multiple microstrip U and L‐shaped open stub resonators patterned in a unique configuration. The proposed configuration aids in capturing more data in a reduced space as well as tunable frequency operation. Tag and reader antennas utilize techniques such as stepped impedance feeding line, defective partial ground plane, and stair‐step patch structure to achieve wide‐band impedance bandwidth in miniature size. The results of the wireless measurements in the non‐anechoic environment show that the proposed system has a reading range of more than 20 cm. The presented system possesses great potential for low‐cost short‐range inventory tracking.